2010
DOI: 10.1007/s12687-010-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants at the APOE, lipoprotein lipase (LpL), cholesteryl ester transfer protein (CETP), and endothelial nitric oxide (eNOS) genes and coronary artery disease (CAD): CETP Taq1 B2B2 associates with lower risk of CAD in Asian Indians

Abstract: Coronary artery disease (CAD) arises due to a complex interplay between the environment and genetic factors. Alterations in many of the biomarkers such as lipids and lipoprotein levels are characteristic of CAD. The phenotypes themselves have genetic determinants, and many single-nucleotide polymorphisms (SNPs) have been identified which influence them. The current study aims to evaluate the effect of six common polymorphisms at four loci, lipoprotein lipase (D9N, N291S, S447X), apolipoprotein E (APOE), choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
5
11
2
Order By: Relevance
“…Similar to the findings of Bhanushali & Das [34] in South Indians, the N291S polymorphism was not detected in our study, although this variant has been reported to be associated with dyslipidemia, DM and coronary artery disease in a meta-analysis [35].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the findings of Bhanushali & Das [34] in South Indians, the N291S polymorphism was not detected in our study, although this variant has been reported to be associated with dyslipidemia, DM and coronary artery disease in a meta-analysis [35].…”
Section: Discussionsupporting
confidence: 89%
“…Among these studies, 28 involved CAD [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 44 , 46 , 47 , 50 , 52 , 53 , 54 , 55 , 59 , 60 , 61 , 66 ], three involved IS [ 63 , 64 , 65 ], and 14 involved MI [ 33 , 40 , 41 , 42 , 43 , 45 , 48 , 49 , 51 , 56 , 57 , 58 , 62 ]. In addition, there were 26 studies on Caucasians [ 23 , 24 , 25 , 27 , 30 , 38 , 39 , 40 , 41 , 42 , 43 ...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were 26 studies on Caucasians [ 23 , 24 , 25 , 27 , 30 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 50 , 51 , 53 , 56 , 57 , 58 , 60 , 62 , 63 , 64 ] and 19 studies on Asians [ 26 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 46 , 49 , 52 , 54 , 55 , 59 , 61 , 65 , 66 ]. Controls of 23 studies were hospital-based [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ,…”
Section: Resultsmentioning
confidence: 99%
“…All the eligible studies were published between 1991 and 2012.There were 20 studies performed in Asian subjects [ 11 , 38 , 47 , 51 , 57 , 58 , 60 , 63 , 65 , 66 ], 26 in Caucasian subjects [ 17 , 20 - 22 , 36 , 37 , 40 - 46 , 49 , 50 , 52 - 56 , 59 , 61 , 62 , 64 , 67 ] and one mixed- population study [ 48 ]. In consideration of the study design, 6 studies were prospective [ 20 , 40 , 43 , 45 , 49 ] and the remaining 41 studies were retrospective [ 11 , 17 , 21 , 22 , 36 - 38 , 41 , 42 , 44 , 46 - 48 , 50 - 67 ]. In addition,11 of the 47 studies were P-B [ 20 - 22 , 36 , 37 , 40 , 43 , 46 , 49 , 54 ] and the remaining studies were H-B [ 11 , 17 , 38 , 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 -…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the study design, 6 studies were prospective [ 20 , 40 , 43 , 45 , 49 ] and the remaining 41 studies were retrospective [ 11 , 17 , 21 , 22 , 36 - 38 , 41 , 42 , 44 , 46 - 48 , 50 - 67 ]. In addition,11 of the 47 studies were P-B [ 20 - 22 , 36 , 37 , 40 , 43 , 46 , 49 , 54 ] and the remaining studies were H-B [ 11 , 17 , 38 , 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 - 53 , 55 - 66 ]. CAD was regarded as the main outcome in most of the studies [ 11 , 17 , 21 , 22 , 36 - 40 , 42 , 44 , 45 , 47 , 49 - 51 , 53 , 55 - 61 , 64 - 66 ], except 8 studies analyzed MI [ 20 , 43 , 46 , 48 , 52 , 54 , 62 , 63 ] and 2 studies analyzed ACS [ …”
Section: Resultsmentioning
confidence: 99%